Handbook of epilepsy - Browne, Thomas R. (Lippincott Williams & Wilkins, 2000)
The thoroughly updated Second Edition of this popular handbook is a practical, accessible, contemporary guide to the diagnosis and management of epilepsy. Written by noted specialists in adult and pediatric epilepsy, the book provides concise yet complete information on the syndromes occurring in each age group, the differential diagnosis of various seizure types, and the pharmacological and surgical therapies available.